Age and growth properties of acanthobrama marmid heckel, 1843 population inhabiting uzuncayir damlake (Tunceli/Turkey) - Coban, Mehmet Zulfu; Yuksel, Fahrettin (My University, 2013)
This study was aimed to investigate the some growth properties of Acanthobrama marmid Heckel, 1843 population in Uzuncayir Dam Lake (Tunceli/Turkey) between May 2011 to September 2012. A total of 604 A. marmid samples (340 males and 264 females) were caught from Uzuncayir Dam Lake; the age composition of the specimens ranged between 1-9 years. The overall sex ratio (females/males) was 1:0.78. Total lengths of specimens ranged from 8.80-27.80 cm and weights ranged from 6.20-182.00 g. The von Bertalanffy growth parameters wereL? = 28.25 cm, K = 0.26 year-1 andt0 =-0.90 year for males andL? = 28.49 cm, K = 0.23 year-1 and t0 =-1.24 year for females. The length-weight relationship was found as W = 0.009xTL3.009 in males and W = 0.012*TL2.926in females. The growth performance index (?') values of males, females and all samples were 2.317, 2.271 and 2.301, respectively. The condition factor values varied between 0.61-1.30 for entire population. © Medwell Journals, 2013.
Keywords: Acanthobrama marmid; Age; Condition factor; Growth parameter; Uzuncayir dam lake